1995
DOI: 10.1016/0016-7061(94)00079-p
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of class and continuous pedotransfer functions to generate soil hydraulic characteristics

Abstract: Class pedotransfer functions were used to generate average hydraulic characteristics for distinct soil texture classes. Continuous pedotransfer functions were used to generate soil hydraulic characteristics from the actually measured median of the sand particle size, bulk density and percentages clay, silt and organic matter. Both approaches were used to predict the soil physical input data to calculate five different functional aspects of soil behaviour. The functional aspects were: number of workable days, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
0
8

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(113 citation statements)
references
References 15 publications
(12 reference statements)
2
103
0
8
Order By: Relevance
“…Similarly, increasing the complexity of data inputs to a model, such as by moving from pedotransfer functions to measured data, can likewise improve the performance of that model. Wösten et al (1995) suggested that more complex soil data be employed only when the differences in estimates of soil behaviour were significant as a consequence. Mohamed and Ali (2006) found that using more detailed input data in PTFs increased their reliability.…”
Section: Soil Physical Data Inputsmentioning
confidence: 99%
“…Similarly, increasing the complexity of data inputs to a model, such as by moving from pedotransfer functions to measured data, can likewise improve the performance of that model. Wösten et al (1995) suggested that more complex soil data be employed only when the differences in estimates of soil behaviour were significant as a consequence. Mohamed and Ali (2006) found that using more detailed input data in PTFs increased their reliability.…”
Section: Soil Physical Data Inputsmentioning
confidence: 99%
“…Vereecken et al (1992) found that estimation accuracies of PTFs for van Genuchten parameters ranged between 0.560 and 0.848 (R 2 ). Wösten et al (1995) derived PTFs for estimation of these parameters in sandy soils with the accuracy of R 2 = 0.71, 0.53, and 0.63 for θ s , α, and n, respectively. Wösten et al (2001) reported that the equation accuracies were 0.76, 0.20, and 0.54 for the same parameters.…”
Section: Resultsmentioning
confidence: 99%
“…In point estimation, soil water contents are estimated at selected water potentials (Batjes 1996, Pachepsky et al 1996, Minasny et al 1999. The parameterization method estimates the parameters of soil water retention models (Vereecken et al 1992, Wösten et al 1995, Schaap et al 1998, Minasny and McBratney 2002. Two of the most commonly used water retention models are van Genuchten (1980) and Brooks and Corey (1964).…”
mentioning
confidence: 99%
“…A talajcsoportok kialakítása többféleképpen történ-het. A módszerek többségében a fizikai féleség adja az osztályozás alapját BRUAND et al, 2003;TÓTH et al, 2005;PACHEPSKY et al, 2006;BAKER, 2008;WÖSTEN et al, 1995). Csoportképző lehet még a talaj szervesanyag-tartalma , szerkezete (PACHEPSKY & RAWLS, 2003), a talaj altípusa (TÓTH et al, 2005;MAKÓ & TÓTH, 2007), vagy taxonómiai kategóriája (BATJES, 1996;), a feltalaj és az altalaj (WÖSTEN et al, 1990;RAWLS et al, 2001), vagy a talajképző kőzet (PACHEPSKY & RAWLS, 2004).…”
Section: Pedotranszfer Függvényekunclassified